2022
DOI: 10.3389/fnins.2022.1004027
|View full text |Cite
|
Sign up to set email alerts
|

The visual basis of reading and reading difficulties

Abstract: Most of our knowledge about the neural networks mediating reading has derived from studies of developmental dyslexia (DD). For much of the 20th C. this was diagnosed on the basis of finding a discrepancy between children’s unexpectedly low reading and spelling scores compared with their normal or high oral and non-verbal reasoning ability. This discrepancy criterion has now been replaced by the claim that the main feature of dyslexia is a phonological deficit, and it is now argued that we should test for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…The right frontoparietal system is a crucial component of the network subserving the automatic shifting of attention [89,90], and developmental changes in its activation have been linked to reading skills in both children with DD [91,92] and TRs [93]. Accordingly, alterations in M input processing in the dorsal visual stream and a consequent dysfunction of the main frontoparietal attentional network, are associated with a sluggish attentional shifting (SAS) [86] and a deficit in perceptual noise exclusion [82,83] in DD [48,52,53,94]. Irrelevant lateral letters should be filtered out by accurate and rapid shifts in spatial and temporal visual attention before the letter-to-sound mapping mechanism is applied [95][96][97][98][99][100][101][102].…”
Section: Discussionmentioning
confidence: 99%
“…The right frontoparietal system is a crucial component of the network subserving the automatic shifting of attention [89,90], and developmental changes in its activation have been linked to reading skills in both children with DD [91,92] and TRs [93]. Accordingly, alterations in M input processing in the dorsal visual stream and a consequent dysfunction of the main frontoparietal attentional network, are associated with a sluggish attentional shifting (SAS) [86] and a deficit in perceptual noise exclusion [82,83] in DD [48,52,53,94]. Irrelevant lateral letters should be filtered out by accurate and rapid shifts in spatial and temporal visual attention before the letter-to-sound mapping mechanism is applied [95][96][97][98][99][100][101][102].…”
Section: Discussionmentioning
confidence: 99%
“…They were created from words by changing one grapheme at a time; *chuse); (4) Consonant strings (CS; sequences that are orthographically illegal and phonologically unpronounceable, since they contain no vowels and therefore no syllables; *nbvrzc). Consonant strings were matched with words based on their form, with respect to the ascender or descender graphemes that they contain; (5) Symbol strings (SS; non-alphabetic stimuli; § ¥Đ ‡). Symbol strings were matched for the number of characters with high frequency words.…”
Section: Linguistic Materialsmentioning
confidence: 99%
“…The main cause of dyslexia is considered to be the phonological de cit, i.e., a di culty in the use of grapheme-to-phoneme conversion rules [1][2][3] . However, many researchers query whether a phonological de cit is the only cause of dyslexia [4][5][6] . Other theories such as auditory de cits 7 , working memory impairment 8 , attentional abnormalities 9 and magnocellular abnormalities 10 have been proposed as alternative explanations.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with dyslexia exhibit impaired time perception across a diverse range of tasks [ 7 ]. Compared to typically developing (TD) controls, children with dyslexia (DD) display increased inaccuracy and variability in beat-related tasks [ 3 ], inconsistencies in the neural representation of auditory beats [ 8 ], as well as reduced neural synchronization (entrainment) to visually [ 9 ] and multimodally presented rhythms [ 10 ]. Correlational studies have indicated that beat perception is associated with performance in reading and reading-related tasks, such as pseudoword decoding [ 11 ], Rapid Automatized Naming [ 11 , 12 , 13 ], phonological awareness [ 14 , 15 ], and letter-to-sound knowledge [ 15 ], in both TD individuals and those with dyslexia [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%